The lymphocyte transformation test in allergic contact dermatitis: New opportunities. (2nd January 2016) - Popple, Amy; Williams, Jason; Maxwell, Gavin; Gellatly, Nichola; Dearman, Rebecca J.; Kimber, Ian
Abstract: Allergic contact dermatitis (ACD) is driven by the activation and proliferation of allergen-specific memory T-lymphocytes and is currently diagnosed by patch testing with a selected panel of chemical allergens. The lymphocyte transformation test (LTT) can be used to monitor ex vivo T-lymphocyte responses to antigens, including contact allergens. The LTT is not viewed as being an alternative to patch testing, but it does seek to reflect experimentally skin sensitization to specific chemicals. The LTT is based on stimulation in vitro of antigen-driven T-lymphocyte proliferation. That is, exposure in culture of primed memory T-lymphocytes to the relevant antigen delivered in an appropriate configuration will provoke a secondary response that reflects the acquisition of skin sensitization. The technical aspects of this test and the utility of the approach for investigation of immune responses to contact allergens in humans are reviewed here, with particular emphasis on further development and refinement of the protocol. An important potential application is that it may provide a basis for characterizing those aspects of T-lymphocyte responses to contact allergens that have the greatest influence on skin sensitizing potency and this will be considered in some detail.